Karakteristik dan Kelimpahan Mikroplastik pada Ikan Pelagis di Pasar Ikan Provinsi Bali - Safitri, Ni Made Adhy; Hendrawan, I Gede; Giri Putra, I Nyoman (Journal of Marine Research and Technology, 2022)
Used Plastic is dumped carelessly into the river, eventually ending up in the sea. Plastic waste has accumulated and been floating in the ocean for a long time can cause the debris to degrade into tiny particles called microplastics. The impact of microplastics is the contamination of marine biota such as fish, driving damage to the digestive tract, reducing growth rates, inhibiting enzyme production, and can affect reproduction and cause physical and chemical damage such as damage to the immune system and blockage of the digestive tract. The study was conducted to determine the characteristics and abundance of microplastics in pelagic fish in the fish market. Microplastics were identified and analyzed using descriptive statistics. Eight types of fish were found: Decapterus macarellus, Sarda orientalis, Selar boops, Sardinella lemuru, Auxis spp ., Hemiramphus lutkei, Selar crumenophthalmus, and Megalaspis cordyla. From 144 fish samples collected from the fish market, 94 fish were contaminated with microplastic, and 50 fish were not contaminated. There are four types: film, fiber, fragment, foam, and fiber macroplastics. The highest abundance was found in Selar boops 2.00 ± 2.44, and the lowest was in Hemiramphus Lutkeni 0.89 ± 0.76.